Comprehensive mapping of SARS-CoV-2 interactions in vivo reveals functional virus-host interactions - Siwy Ling Yang (Nature Portfolio, 2021)
Here, Yang et al. apply different RNA sequencing approaches to characterize the secondary structure of SARS-CoV-2 viral RNAs, report on long-range interactions along the viral genome, and uncover the virus-host RNA interactome in cells.